PERBANDINGAN PEMAKAIAN BAHAN BAKAR CAMPURAN TERHADAP KINERJA MESIN BENSIN 4 TAK - Wibowo, Hary; Ristanto, Yudi Ari (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
The ethanol and methanol are derivative compound of alcohol with 115 and 111 octane number, respectively.The blend of both to premium to descrease of their octane number. This research of premium ethanol fuel with 80% premium-20% ethanol composition and premium methanol fuel with 77% premium-23%methanol composition also biopremium Pertamina with 95% premium-5%ethanol composition. The aim of this research to know the performance of engine (torque, power, mean effectif pressure, fuel conversion efficiency), and also emission of exhaust gas (CO,CO2, HC, and O2). The experiment device is Honda Grang C100 motorccle with Twin Chassis Dynamometer methode on variable velocity, 4000 rpm, 5000 rpm, 6000 rpm,7000 rpm, 8000 rpm, and 9000 rpm respectively. The result and calculated of this research indicated that torque, power, mean effectif pressure, and fuel conversion efficiency on the mixed of premium-ethanol 5.71%, 4.91%, 9,58% higher then premium fuel,respectively. The consumption of premium-ethanol mixed fuel 9.1% less then premium fuel. The premium-methanol mixed used indicated that CO (carbon monoxyde) 52.56% less, CO2 (carbon dioxide) 27,82% higher, O2 (oxygen) 11.87% less, then premium fuel used, respectively. Used of biopremium Pertamina fuel indicated that HC (hydrocarbon) 29.78% less then premium fuel.